Indicators of disability resulting from urological diseases among patients in Ukraine and its regions - Driianska, V.; Pasyechnikov, S.; Nurimanov, K.; Mitchenko, M.; Startseva, L.; Kononova, G.; Sevastyanova, N.; Shulyak , O. (Ukrainian Journal of Nephrology and Dialysis, 2024)
The purpose of the work was to analyze the dynamics of indicators of primary disability due to diseases of the genitourinary system among the adult population of Ukraine, to determine regional features, including depending on age and established groups. Materials and methods. The dynamics of the absolute and relative data of those initially recognized as disabled due to diseases of the genitourinary system in Ukraine and five regions as a whole from 2018 to 2022 years are presented, comparing the results of 2008. The peculiarities of the indicators of the regions and Kyiv were analyzed, for which official reporting data was used, and collections on the main indicators of urological care in Ukraine. Results. A significant increase in the absolute and relative number of initially recognized disabled persons in adulthood, including among persons of working age, was established, both in the period 2018-2022 and during 15 years when comparing 2022 and 2008 (p<0.001); the largest percentage is registered in the Western and South-Eastern regions. Most of the initially recognized disabled persons for the period 2018-2022 years are of working age - the average pre-retirement period and up to 40 years, and there is no significant difference between this period (р>0.05); over the past 15 years, there has been a trend towards an increase in disabled persons of retirement age (p=0.087). In the 2022 year, Kyiv ranked first in terms of the percentage of disabled people of retirement age, which increased for the period 2008-2022 years from 9.5 to 34.2% (p<0.001) due to a decrease - up to 40 years old, the indicators significantly exceeded those compared to all regions (p <0.05) except for North-East (p=0.161). Probable growth in 2018 and 2022 of the relative number of disabled people in the 1st grade compared to 2008 is shown - both in Ukraine as a whole (p=0.004 and p=0.004, respectively), and in each region (p<0.05) and Kyiv ( (p<0.001 and 0.002), which is an important medical and social problem. Conclusions. The determined indicators of disability and their regional features allow us to substantiate the relevant programs for the development of the urological service for the prevention and timely treatment of diseases of the genitourinary system in order to reduce the share of the disabled population and improve their quality of life.